(untitled) (Journal of history, 2019)
The article deals with the formation of the ideas of national statehood in the activities of intellectuals of Alash in the key of modern research. This topic has long studied by historians, philologists but has not lost its relevance. Therefore, the authors analyze the problems of formation of the national idea, which in Soviet times was on the ban. Also, the article describes the works of not only local historians and the study of foreign scholars on the issue of acquisition of Alash movement for national autonomy. An analysis of the scientific works of the representatives of the national intelligentsia